Reverse Logistics Performance Assessment in the Construction Industry Sector - Farida Pulansari; Nur Rahmawati; Isna Nugraha; Amelia Ramadhani Ardysti; Handy Natan Permana; Jafni Fara Zahirah (Future Science, 2022)
The number of emerging furniture construction industries and the limited availability of virgin materials force companies to innovate both in terms of products and services provided. One way that can be done is through reverse logistics. Reverse logistics itself has many advantages both for the company, for the sustainability of virgin material and for the surrounding environment. PT. X is a company engaged in furniture construction. The company is currently implementing reverse logistics. However, there has never been an assessment of the effectiveness of its implementation. In this research, an analytical approach is used to measure the effectiveness of RL implementation by using a reverse logistic maturity framework. The result from the assessment based on the reverse logistic maturity framework conducted, PT. X categorized in to developed level.